2010
DOI: 10.1016/j.jpainsymman.2009.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Gynecological Cancer Patients During and After Anticancer Treatment

Abstract: We recommend you cite the published version. The publisher's URL is http://dx.doi.org/10. 1016/j.jpainsymman.2009.06.011 Refereed: No (no note) Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited.UWE makes no representation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 100 publications
6
34
0
Order By: Relevance
“…In line with previous studies (e.g., Goedendorp et al, 2008;Prue et al, 2009), psychological factors such as depression and stress play a key role in fatigue before treatment. It is possible that patients' psychological reaction to their cancer diagnosis and apprehension about impending treatments contributed to higher perceived psychological distress and thereby fatigue.…”
Section: Predictor Variablessupporting
confidence: 87%
See 1 more Smart Citation
“…In line with previous studies (e.g., Goedendorp et al, 2008;Prue et al, 2009), psychological factors such as depression and stress play a key role in fatigue before treatment. It is possible that patients' psychological reaction to their cancer diagnosis and apprehension about impending treatments contributed to higher perceived psychological distress and thereby fatigue.…”
Section: Predictor Variablessupporting
confidence: 87%
“…Those that have been conducted to date have largely been cross-sectional, have focussed on a limited number of possible contributing factors and have produced conflicting findings. Prue et al (2009) reported that distress, physical symptom distress and overall valuation of life predicted fatigue prior to adjuvant therapy in gynaecological cancer patients, while activity levels made no significant contribution. In contrast, Goedendorp et al (2008) reported that physical activity, but not anxiety, predicted severe fatigue before treatment in a large sample of cancer patients with various malignancies, although significant differences in anxiety between fatigued and non-fatigued participants were noted.…”
mentioning
confidence: 95%
“…It has been shown, in a large longitudinal study of patients with chronic lymphatic leukaemia, that the only predictive variable for persistent fatigue was fatigue at the end of treatment (Heutte et al , 2009). Another study in patients with gynaecological cancer identified 12 months psychological distress as the only relevant correlate of fatigue during anticancer treatment (Prue et al , 2010), which is in essence a similar result. However, although predictor analysis is interesting, the knowledge of prevalence rates in different subgroups is of high clinical importance too.…”
Section: Discussionmentioning
confidence: 84%
“…In earlier symptom studies of cancer patients, fatigue was the most commonly seen in more than 91% of the patients; this is consistent with earlier studies. 19, 20 …”
Section: Discussionmentioning
confidence: 99%